ENHANCING SECOND LANGUAGE ACQUISITION: EXPLORING THE INTEGRATION AND INFLUENCE OF TECHNOLOGY ON LANGUAGE LEARNING AND ACQUISITION (Contemporary Journal of Social Science Review, 2025)
The present research focuses on how students integrate technology in teaching and learning of English language and how does technology influence language learning and acquisition. A total of thirty students of English Department responded to the online non-probabilistic semi-structured questionnaire to obtain data through the qualitative research methods. The research focuses on the possibility of enhancing second language acquisition through the integration of technological tools such as the AI applications, virtual conference and language learning programs. The findings point to the fact that self-paced learning is highly aided by technology, that real resources are more easily accessed than fake and that using the assets increases terminology, speaking and general language proficiency. However, students and their responses also described the benefits of the technological factor, such as freedom and individual approach. The analysis shows areas for improvement and more research into increasing the use of innovation in learning languages, and at the same time demonstrates the potential of technology in creating vibrant and equitable learning environments.